Effects Of Temperature In Alpha Decay - Pérez Velásquez, J.E. (2023)
One of the processes relevant in a nucleosynthesis calculation is the alpha decay (a-decay) of heavy nuclei. In this work, the alpha decay process is investigated in an astrophysical environment by introducing temperature dependence in the calculation of half-lives. By using a simple model based on the semiclassical treatment of the alpha decay process, the half-lives are evaluated by considering an alpha particle, which tunnels through the Coulomb barrier generated by its interaction with the daughter nucleus. We find the temperature dependent half-lives for several isotopes and compare them with the results obtained in a previous work. It is concluded that including temperature leads to a reduction in alpha decay half-lives. However, the magnitude of the reduction depends on the approach used.